Co-movement between Malaysian stock index and bond index: empirical evidence from rank tests for cointegration - Lim, Shiok Ye; Ong, Seue Li; Ho, Chong Mun (Elsevier, 2012)
This study aims at examining the long-run cointegration relationship for Malaysian stock and bond market indices in the period surrounding the Asian financial crisis based on the Breitung (2001) rank test procedures. The paper argues that the standard cointegration tests do not allow for breaks and lead to the finding of no cointegration. Breitung (2001) rank test was applied which can tackle the problem of breaks and can detect both linear and nonlinear cointegration relationships. For the full period (1994:1 to 2009:9) and sub-period (2000:1 to 2009:9), findings on the co-movement of stock index and bond indices suggest a long-run equilibrium relationship between these indices.